Endoscopic ultrasound-guided pelvic abscess drainage: a report of 2 cases and literature review - Ouyang, Bo-wen; Liu, Tian-wen; Fu, Zao-li; Li, Ye; Zhang, Beiping (Zeitschrift für Gastroenterologie, 2021)
Background Drainage is essential for source control of the infection in a pelvic abscess. The purpose of this study was to report 2 cases of endoscopic ultrasound (EUS)-guided drainage of the pelvic abscess and review the literature of different modalities of EUS-guided drainage of pelvic abscess.Case presentation A 60-year-old male developed a pelvic abscess 1 month after laparoscopic complete tumor resection. An abdominal CT showed a mass shadow (about 7.1 cm × 5.1 cm) in the right pelvic region. Another case was an 85-year-old male who developed a pelvic abscess 3 days after recurrent tumor resection of multiple organs. The CT showed pelvic effusion and gas accumulation (approximately 6.5 cm × 4.2 cm), and the intestinal tube above the small intestinal anastomosis was dilated with effusion. A 19G-A puncture needle was used to puncture the abscess. An 8-mm cylindrical balloon was inserted, followed by a 10 Fr-3 cm double pigtail stent and an 8.5 Fr drainage tube. After EUS-guided drainage of pelvic abscess, the symptoms disappeared without recurrence.Conclusions EUS-guided drainage is an effective and safe method for treating pelvic abscesses as long as the drainage modality is appropriately selected based on the etiology, size, and mucus viscosity of the abscess.
Keywords: Drainage; Beckenabszess; Ultraschall-gesteuerte Drainage; Drainagemethode; Symptome